Pedal force and power output during sprint cycling at different loads on a cycle ergometer - Coleman, S. G.; Hale, T. (1999)
The aim of this study was to investigate the effects of different ergometer resistance on the force, torque and power outputs during a 10s. sprint. Nine elite sprint cyclists of age 26.5± 2.8 yr., mass 82.0± 6.6 kg and height 1.80± 0.06 m. (mean± S.D.) performed a set of randomly-assigned sprints against different loads (7,8,9,10,11,12,13% body mass) on a modified Monark 864 cycle ergometer fitted with a pair of piezo-electric force pedals (Coleman and Hale, 1998). Orthogonal forces from each pedal, pedal angles and crank angle were all recorded at 100Hz. These were used to calculate effective (tangential) and ineffective (radial) pedal forces, as well as crank torques and power outputs.